Best wishes ebook - Golden, Christopher (Dark Horse Comics, LLC., 2018)
When two strangers cast coins in a Central Park fountain, their dreams and desires become supernaturally intertwined. Cal wants fame and respect and Mary craves true love from her pro quarterback boyfriend, but destiny weaves a tangled fabric. From Mike Richardson (47 Ronin, Echoes) and Eisner Award winner Paul Chadwick (Concrete, The World Below) comes Best Wishes, a Woody Allen-esque tale of New York, meme madness, fame's price, and secrets of the heart.